Get the Ego Advantage! - Sen, Anjana, 1957- (New Delhi Response Books, 2006)
What is this Ego and why is there so much of it everywhere?' Our ego is like an invisible but tangible bubble which we project around ourselves, based on our own impression of our abilities and worth. This book shows how our abilities and sense of worth combine in the ego to determine our actions and interactions.
Include Illustrations
Keywords: Self-actualization (Psychology) -- Self-confidence -- Ego (Psychology)